Cancer-associated fibroblasts induce monocytic myeloid-derived suppressor cell generation via IL-6/exosomal miR-21-activated STAT3 signaling to promote cisplatin resistance in esophageal squamous cell carcinoma - Zhao, Qitai; Huang, Lan; Qin, Guohui; Qiao, Yamin; Ren, Feifei; Shen, Chunyi; Wang, Shumin; Liu, Shasha; Lian, Jinyao; Wang, Dan; Yu, Weina; Zhang, Yi (Cancer letters, 2021)
Drug resistance remains the major obstacle limiting the effectiveness of chemotherapy for esophageal squamous cell carcinoma (ESCC)[1]. However, how stromal cells cooperate with immune cells to contribute to drug resistance is not yet fully understood. In this study, we observed that monocytic myeloid-derived suppressor cells (M-MDSCs) were correlated with cisplatin resistance in patients with ESCC. Furthermore, CAFs promoted differentiation of monocytes into M-MDSCs phenotypically and functionally in vitro. Mechanically, both interleukin (IL)-6 and exosome-packed microRNA-21 (miR-21) secreted by CAFs synergistically promoted the generation of M-MDSCs via activating the signal transducing activator of transcription 3 (STAT3) by IL-6 in an autocrine manner. Combined blocking of IL-6 receptor and inhibition of miR-21 significantly reversed CAF-mediated M-MDSC generation. Notably, the effects of CAFs on M-MDSC induction were abolished by inhibiting STAT3 signaling. Functionally, CAF-induced M-MDSCs promoted drug resistance of tumor cells upon cisplatin treatment. Clinically, ESCC patients with high infiltration of CAFs and CD11b+ myeloid cells had unfavorable predicted overall survival both in our cohort and in TCGA data. Taken together, our study reveals a paracrine and autocrine of IL-6 caused by CAFs co-activate STAT3 signaling, promoting the generation of M-MDSCs, and highlights the important role of CAFs in cooperation with M-MDSCs in promoting drug resistance, thus providing potential opportunities for reversing drug resistance through inhibition of STAT3 signaling. •Cancer-associated fibroblasts(CAFs) promoted M-MDSCs generation through activating STAT3 signaling by IL-6 in paracrine and exosomal-miR-21 medicated of autocrine in monocytes.•Monocytic myeloid-derived suppressor cells (M-MDSCs) mediated cisplatin resistance of esophageal squamous cell carcinoma(ESCC).•Co-infiltration of M-MDSCs and CAFs predict a poor survival of ESCC in our clinical cohort and TCGA dataset.